Law Enforcement Against Business Actors Who Cause Water Pollution - Astuti, Hesti Dwi; Yulianah, Yuyun; Safitri, Isti (Golden Ratio of Law and Social Policy Review, 2023)
This research aims to examine law enforcement against business actors who cause water pollution in Cianjur Regency. Today's rapid development has a negative impact on the environment. Liquid waste from industry and domestic is the main cause of water pollution, which threatens the quality of water used as a source of daily needs. This research uses a normative juridical approach and descriptive analysis method. Data is obtained through literature studies by searching for primary materials and supported by secondary materials. The impacts of water pollution by business actors include: a decrease in the quality of water resources, public health problems, and losses for farmers. The implementation of law enforcement against business actors is faced with several obstacles, including the lack of awareness of the importance of the environment and the lack of effective criminal sanctions. To maintain the right to a good and healthy environment, serious environmental protection and management as well as strict law enforcement are required by all parties concerned. Obstacles in law enforcement against business actors who commit water pollution include non-optimal environmental protection and management, violations of existing regulations, and obstacles in the waste filtration process. Therefore, decisive action is needed in law enforcement, including operational requirements, waste treatment, and more effective supervision to control and prevent water pollution in Cianjur Regency.